2008
DOI: 10.1063/1.2917795
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-density capacitive plasma by the effects of multihollow cathode discharge and high-secondary-electron emission

Abstract: High-density capacitively coupled plasma with electron density of 1011cm−3 was produced with the effects of the multihollow cathode discharge and the high-secondary-electron emission from radio frequency (rf)-biased electrode using Ar gas. It was found that the optimum pressure was around 3–15Pa. In the case of only multihollow cathode discharge, the plasma density increased from 1.2×1010to8×1010cm−3 with the increasing distance z from the cathode electrode for 5mm<z<15mm. Moreover, plasma densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…For example, the effects of the hole diameter (ranging from 0 to 10 mm), the driving frequency and gas composition on the RF MH cathode discharge have been studied by several authors [29,30,32,33]. Ohtsu et al [34] have used MH cathode discharges with small diameter (D = 5 mm) and depth (W = 15 mm) of holes to achieve the high-growth rate of amorphous hydrocarbon (a-C:H) thin films. In reference [35], the authors used the parallel plates form of an RF hollow cathode, with cathode-to-cathode distance equal to 45 mm for deposition of diamond like carbon (DLC) thin films.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effects of the hole diameter (ranging from 0 to 10 mm), the driving frequency and gas composition on the RF MH cathode discharge have been studied by several authors [29,30,32,33]. Ohtsu et al [34] have used MH cathode discharges with small diameter (D = 5 mm) and depth (W = 15 mm) of holes to achieve the high-growth rate of amorphous hydrocarbon (a-C:H) thin films. In reference [35], the authors used the parallel plates form of an RF hollow cathode, with cathode-to-cathode distance equal to 45 mm for deposition of diamond like carbon (DLC) thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value for the latter case is ten times higher than that for the former case. This is caused by the previously proposed high secondary‐electron emission 8. This value is the best data in the capacitively coupled plasma CVD using pure methane gas.…”
Section: Resultsmentioning
confidence: 58%
“…This is caused by the previously proposed high secondaryelectron emission. [8] This value is the best data in the capacitively coupled plasma CVD using pure methane gas. Figure 3 shows the radial profile of the deposited films for hollow electrodes of set-ups A and E. Here, the methane gas pressure is 5 Pa, the injected RF power is 200 W, and the substrate biased voltage V b ¼ À300 V. The process time is 60 min.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Ohtsu and Fujita also found that high density capacitively coupled plasma (CCP) with electron density of 10 11 cm À3 can be produced with the effect of high SEE coefficient. 14 Recently, Lafleur et al investigated the discharge phenomenon in low pressure RF discharge using a simple analytical model together with a 1D particle in cell simulation. Their results indicated that it is possible to generate an asymmetric plasma response in a geometrically symmetric, RF capacitive plasma.…”
Section: Introductionmentioning
confidence: 99%